Marcadores microssatélites para os genomas nuclear e organelar de amburana cearensis (Allemão) A.C. Smith - Santos, Laís Souza (2021)
Amburana cearensis is a tree species, popularly known in Brazil as cerejeira, widely distributed in Brazil and also in Argentina, Bolivia, Paraguay and Peru. The species is distributed in a range of intense anthropic action and classified as endangered according to the International Union for the Conservation of Nature (IUCN). The economic demand for A. cearensis as a wood source and medicinal source has boosted its predatory exploitation, representing a threat to the survival of the species. In this scenario, conservation genetics is essential for generating knowledge about the genetic diversity of the species and defining appropriate strategies for its conservation and management. The general objective of this work was to design primer pairs with high potential for the development of robust and informative microsatellite markers for the nuclear, chloroplast and mitochondrial genomes of A. cearensis. Moreover, for quickness and cost savings, nuclear microsatellite primer pairs were designed for amplification in multiplex PCR. To achieve the proposed objectives, the genome of A. cearensis was partially sequenced, using the Illumina MiSeq platform. The assembly of the genomic library was performed from the DNA of an individual of the species and the genomic sequences obtained were analyzed using FastQC, Trimmomatic and DipSPAdes software. The search for microsatellite regions was performed using the QDD program. Thirty pairs of primers for nuclear microsatellite regions were designed, organized into five sets for amplification in multiplex PCR. The primer pairs designed in this study have the potential to generate new microsatellite markers with high individual discrimination capacity and transferability to other species of the genus Amburana. These markers can be applied quickly and efficiently for different types of genetic diversity studies of A. cearensis and Amburana genus.